Evaluating performance measures for the bobsleigh push start - Zedler, M.; Braunstein, B.; Potthast, W.; Goldmann, J.-P. (ISBS Proceedings Archive (Michigan), 2023)
Quantification of performance is essential to understand performance determinants. Therefore, the purpose of this study was to evaluate different performance measures applied to the bobsleigh push start and to discuss the choice of an appropriate measure for research and coaching. Measures based on the change in kinetic energy and based on the change in momentum were calculated for the early acceleration phase during the push start and compared by means of correlation analyses. Both energy-based and momentum-based methods lead to similar results while it is important to consider the athlete and the bob as a system. Further clarification is required on whether the flight phase should be taken into account when calculating performance measures.